(untitled) (Global Scientific Review, 2025)
In an era of increasing global interconnectedness, the influence of English on various languages worldwide has become a prominent phenomenon. This study explores the assimilation of Anglicisms—English loanwords and phrases—into Uzbek and Dari, two distinct but related languages spoken in Central and South Asia. By analyzing lexical and morphological adaptations in both languages, this research investigates the extent to which English terms are integrated into the native linguistic frameworks of Uzbek and Dari.